Pacemaker‐Mediated Tachycardia: Manufacturer Specifics and Spectrum of Cases. Issue 12 (5th November 2015) - MONTEIL, BENJAMIN; PLOUX, SYLVAIN; ESCHALIER, ROMAIN; RITTER, PHILIPPE; HAISSAGUERRE, MICHEL; KONERU, JAYANTHI N.; ELLENBOGEN, KENNETH A.; BORDACHAR, PIERRE
Abstract : Pacemaker‐mediated tachycardia (PMT) is the term used to describe a repetitive sequence of sensed retrograde P waves followed by ventricular pacing at or below the maximum tracking rate. The following events can promote atrioventricular (AV) dissociation, retrograde conduction, and the onset of PMT: ventricular or atrial extrasystole, an excessively long programmed AV delay, external interference or myopotentials sensed by the atrial channel, atrial sensing or pacing failure, the absence of postventricular atrial refractory period extension after removal of a magnet, and VDD pacing at a higher rate than sinus rate. In contemporary devices, each manufacturer has a proprietary algorithm to detect and terminate PMT. Because of the increase in the number and complexity of the pacing algorithms and because of manufacturer‐driven differences, a basic understanding of these new algorithms is important for patient care. We review here the main elements of the physiopathology of this type of tachycardia, describe the specific characteristics of the different manufacturers, and present representative clinical cases.